Psychological assistance during the coronavirus disease 2019 outbreak in China. (May 2020) - Wang, Yanbo; Zhao, Xudong; Feng, Qiang; Liu, Liang; Yao, Yuhong; Shi, Jingyu
Disaster psychological assistance has become an important part of the disaster relief system, playing a crucial role in restoring and maintaining emotional stability and security of people and reducing trauma-related stress. As the first country to experience the outbreak of the coronavirus disease 2019 (COVID-19), China actively adopted psychological assistance measures in response to the panic caused by the epidemic. These measures are expected to help the Chinese government and governments in other parts of the world to better respond to the outbreaks of COVID-19.